UNILATERAL DIGITAL INCOME TAXATION BASED ON SIGNIFICANT ECONOMIC PRESENCE: AFFIRMING INDONESIA’S FISCAL SOVEREIGNTY IN THE DIGITAL ECONOMY ERA - Muhamad Iqbal Nurrasyid; Haula Rosdiana (ITB AAS Indonesia Surakarta, 2026)
This study examines the choice of income tax instruments for the digital economy and develops a unilateral digital income tax framework grounded in the concept of Significant Economic Presence (SEP) for Indonesia, set against the prolonged impasse of the OECD/G20 Pillar One multilateral solution. Employing a qualitative juridical-normative approach and a literature study, it compares an SEP-based income tax with the Electronic Transaction Tax (PTE) through three lenses: fairness, consistency with international tax norms, and the strengthening of fiscal sovereignty. The analysis finds that SEP is normatively superior because it taxes profit in accordance with the ability-to-pay principle and aligns with the doctrine of economic allegiance, yet it is constrained in formal enforceability because it collides with the permanent establishment definition embedded in tax treaties. The PTE, by contrast, is easier to administer but is prone to being deemed discriminatory and to provoking retaliation. The study therefore proposes mitigating measures comprising a high revenue threshold and a non-discrimination principle, a phased implementation roadmap inspired by the CBAM transition mechanism, and institutional and fiscal-diplomacy strengthening. Its principal contribution is an integrated unilateral framework linking nexus design, treaty-conflict mitigation, and implementation strategy